STUDYING THE ANTIOXIDANT PROPERTIES OF THE STEM AND LEAF PART OF THE PLANT CUCUMIS SATIVUS (Scientific journal of the Fergana State University, 2024)
This article describes a method for studying the biological activity - antioxidant properties of a sample of Cucumis sativis plant powder prepared from a mixture of stem and leaf parts. In the Cucumis sativis sample, epinephrine was assessed by the in vitro autooxidation reaction inhibition method, that is, the ability of epinephrine to inhibit the autooxidation reaction and simultaneously prevent the formation of active oxygen forms (AOF).